2017
DOI: 10.1016/j.ecosys.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Charitable donations by China’s private enterprises

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Given the short duration of the study period, there was hope that if a longer period of data was used, these results may significantly improve. This is particularly because the results of this study were in agreement with similar studies like Esteban-Sanchez et al 2017, Gustafsson et al (2017), and Houqe et al (2019).…”
Section: Empirical Modelsupporting
confidence: 93%
See 1 more Smart Citation
“…Given the short duration of the study period, there was hope that if a longer period of data was used, these results may significantly improve. This is particularly because the results of this study were in agreement with similar studies like Esteban-Sanchez et al 2017, Gustafsson et al (2017), and Houqe et al (2019).…”
Section: Empirical Modelsupporting
confidence: 93%
“…Their results indicated that the level of a company's donations has a significant impact on its share price and its value, and is able to offset any agency conflict that may arise when the decisions of the management to gift is not aligned with the shareholders' value propositions. Results of Houqe et al (2019) corroborated prior findings by Gustafsson, Yang, Shuge, and Jianzhong (2017), who found that corporate donations are related to a company's financial returns.…”
Section: Literaturesupporting
confidence: 57%
“…The signs of the coefficients on control variables echo those in the existing literature. The coefficients on AGE , SIZE , INTANG and PROFIT are significantly positive, indicating that firms with longer age, larger scale, higher proportion of intangible assets and better profit perform better in corporate philanthropy (Amato and Amato, 2007; Du et al , 2014; Gustafsson et al , 2017; Luo et al , 2017; Zhang et al , 2010a; Zheng and Zhang, 2016). The coefficients on POC and DW are also significantly positive, suggesting that entrepreneurs with political connections and higher social status have a higher enthusiasm for corporate philanthropy (Li et al , 2015; Wei et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In firm-specific characteristics, compared with state-owned firms, private firms are more likely to increase the probability and extent of corporate donations (Zhang et al , 2010a). Given that firm’s resource acquisition capability, abundant cash resources and better profitability will boost corporate philanthropy (Gustafsson et al , 2017). Amato and Amato (2007) further find a U-shaped relationship between a firm’s scale and CSR participation, suggesting that medium-sized firms contribute relatively little to charitable donations.…”
Section: Institutional Background Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Our regression includes a set of control variables as follows, which are similar to previous studies (Brammer & Millington, 2008;Chan et al, 2017;Chen et al, 2018;Gustafsson et al, 2017;Iatridis, 2015;Luo et al, 2017;Wei et al, 2018;Zhang et al, 2010). Size is the natural logarithm of assets; Leverage is total liabilities divided by total assets.…”
Section: Regression Modelmentioning
confidence: 99%